Representations of Korean Dramas in Indonesian Audience Discourse: A Topic Modeling Analysis of YouTube Comments - Perdhani Yunia Putri; Purwadi (INJECT (Interdisciplinary Journal of Communication), 2025)
Korean dramas (K-Dramas) have become extremely popular among Indonesian audiences, offering an often idealized and romanticized depiction of Korean culture. This study examines the dynamics of Indonesian audiences’ perceptions of Korean dramas (K-Dramas) by analyzing comments on YouTube videos. This study uses topic modeling analysis to examine Indonesian audiences’ reactions through YouTube comments (85,840 comments from 720 videos). The study began with 15 topics generated by a topic modeling algorithm. Upon further analysis, the study found that several of these topics were closely related, leading to the consolidation of these topics into four broader main topics: (1) K-Drama as Entertainment, (2) Cultural Representations and Social Issues, (3) Personal Relationships and Family Dynamics, and (4) Social Reactions and National Dignity. This research implies that the findings can be used by policymakers and media industry players to develop strategies that support constructive cultural dialogue and develop content with more culturally sensitive narratives.